Спекание высокобористых соединений в условиях высоких давления и температуры - Соколов, А.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
It is shown, that by a sintering at high pressure and temperature is possible to matrix reinforced by rod inclusions of additives. The high pressure and temperature allow to intensify sintering
process.